Intermittent preventive treatment of malaria provides substantial protection against malaria in children already protected by an insecticide-treated bednet in Burkina Faso: a randomised, double-blind, placebo-controlled trial. - Amadou T Konaté; Jean Baptiste Yaro; Amidou Z Ouédraogo; Amidou Diarra; Adama Gansané; Issiaka Soulama; David T Kangoyé; Youssouf Kaboré; Espérance Ouédraogo; Alphonse Ouédraogo; Alfred B Tiono; Issa N Ouédraogo; et al. (PLoS Medicine)
Background Intermittent preventive treatment of malaria in children (IPTc) is a promising new approach to the control of malaria in areas of seasonal malaria transmission but it is not known if IPTc adds to the protection provided by an insecticide-treated net (ITN). Methods and findings An individually randomised, double-blind, placebo-controlled trial of seasonal IPTc was conducted in Burkina Faso in children aged 3 to 59 months who were provided with a long-lasting insecticide-treated bednet (LLIN). Three rounds of treatment with sulphadoxine pyrimethamine plus amodiaquine or placebos were given at monthly intervals during the malaria transmission season. Passive surveillance for malaria episodes was established, a cross-sectional survey was conducted at the end of the malaria transmission season, and use of ITNs was monitored during the intervention period. Incidence rates of malaria were compared using a Cox regression model and generalized linear models were fitted to examine the effect of IPTc on the prevalence of malaria infection, anaemia, and on anthropometric indicators. 3,052 children were screened and 3,014 were enrolled in the trial; 1,505 in the control arm and 1,509 in the intervention arm. Similar proportions of children in the two treatment arms were reported to sleep under an LLIN during the intervention period (93%). The incidence of malaria, defined as fever or history of fever with parasitaemia ≥ 5,000/µl, was 2.88 (95% confidence interval [CI] 2.70-3.06) per child during the intervention period in the control arm versus 0.87 (95% CI 0.78-0.97) in the intervention arm, a protective efficacy (PE) of 70% (95% CI 66%-74%) (p<0.001). There was a 69% (95% CI 6%-90%) reduction in incidence of severe malaria (p = 0.04) and a 46% (95% CI 7%-69%) (p = 0.03) reduction in the incidence of all-cause hospital admissions. IPTc reduced the prevalence of malaria infection at the end of the malaria transmission season by 73% (95% CI 68%-77%) (p<0.001) and that of moderately severe anaemia by 56% (95% CI 36%-70%) (p<0.001). IPTc reduced the risks of wasting (risk ratio [RR] = 0.79; 95% CI 0.65-1.00) (p = 0.05) and of being underweight (RR = 0.84; 95% CI 0.72-0.99) (p = 0.03). Children who received IPTc were 2.8 (95% CI 2.3-3.5) (p<0.001) times more likely to vomit than children who received placebo but no drug-related serious adverse event was recorded. Conclusions IPT of malaria provides substantial protection against malaria in children who sleep under an ITN. There is now strong evidence to support the integration of IPTc into malaria control strategies in areas of seasonal malaria transmission. Trial registration ClinicalTrials.govNCT00738946. Please see later in the article for the Editors' Summary.